2006
DOI: 10.1128/iai.74.4.2224-2232.2006
|View full text |Cite
|
Sign up to set email alerts
|

Immunization with theHaemophilus ducreyiHemoglobin Receptor HgbA Protects against Infection in the Swine Model of Chancroid

Abstract: The etiologic agent of chancroid is Haemophilus ducreyi. To fulfill its obligate requirement for heme, H. ducreyi uses two TonB-dependent receptors: the hemoglobin receptor (HgbA) and a receptor for free heme (TdhA). Expression of HgbA is necessary for H. ducreyi to survive and initiate disease in a human model of chancroid. In this study, we used a swine model of H. ducreyi infection to demonstrate that an experimental HgbA vaccine efficiently prevents chancroid, as determined by several parameters. Histologi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
50
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(53 citation statements)
references
References 64 publications
(60 reference statements)
2
50
1
Order By: Relevance
“…For example, immunoproteomic analysis of the whole cell proteins of Riemerella antipestifer revealed that TonB-dependent receptor was among the immunogenic outer membrane proteins (Q. , and a study with a Znuptake Tdr, ZnuD, of Neisseria meningitidis showed that it could induce bactericidal antibodies upon immunization of mice (Stork et al 2010). Similarly, Tdr with vaccine potentials have been found in Haemophilus ducreyi and, as reported by us, P. fluorescens (Afonina et al 2006, Fusco et al 2010, Leduc et al 2011, Y. Hu et al 2012. In this study, we found that, when used as subunit vaccines, the recombinant proteins rTdr1, rTdr2, and rTdr3 elicited moderate but significant protections that differed in magnitude, with the highest RPS being effected by rTdr3.…”
Section: Discussionsupporting
confidence: 57%
“…For example, immunoproteomic analysis of the whole cell proteins of Riemerella antipestifer revealed that TonB-dependent receptor was among the immunogenic outer membrane proteins (Q. , and a study with a Znuptake Tdr, ZnuD, of Neisseria meningitidis showed that it could induce bactericidal antibodies upon immunization of mice (Stork et al 2010). Similarly, Tdr with vaccine potentials have been found in Haemophilus ducreyi and, as reported by us, P. fluorescens (Afonina et al 2006, Fusco et al 2010, Leduc et al 2011, Y. Hu et al 2012. In this study, we found that, when used as subunit vaccines, the recombinant proteins rTdr1, rTdr2, and rTdr3 elicited moderate but significant protections that differed in magnitude, with the highest RPS being effected by rTdr3.…”
Section: Discussionsupporting
confidence: 57%
“…Whole-cell immunoprecipitation was performed as previously described (11), with pig anti-nHgbA antibodies that recognize surface-exposed epitopes of nHgbA (1). H. ducreyi strains were grown on chocolate agar plates with streptomycin (50 g/ml).…”
Section: Construction Of a Two-dimensional Model Of The Hgba Receptormentioning
confidence: 99%
“…Elimination of chancroid, through either vaccination or diagnosis and antibiotic treatment of core groups, could potentially slow human immunodeficiency virus transmission where both diseases are endemic (26,27). HgbA is a highly effective vaccine in the swine model of chancroid infection (1), and it is conceivable that an HgbA vaccine might be used for the control of chancroid in humans.…”
mentioning
confidence: 99%
“…Bovine Hgb was coupled to Affigel-10 (Bio-Rad, Hercules, CA) as per the manufacturer's instructions. The Hgbagarose was washed and mock eluted before use with elution buffer as previously described (11). Bacteria expressing mutant hgbA in FX547 grown in low-heme GC broth (3 ml at an OD 600 of 1.0) were pelleted, Growth phenotype assay in Hgb-only media.…”
Section: Methodsmentioning
confidence: 99%
“…HgbA is one of three TonB-dependent transporters (TBDT) present in the genome of prototypical strain 35000HP and the only TBDT absolutely necessary to establish infection in the human experimental model of chancroid (9,10). Immunization with native HgbA (nHgbA) prevents infection in the experimental swine model of chancroid (11,12). Furthermore, passive immunization with HgbA antisera protects against an experimental challenge, suggesting that vaccine protection is mediated by the humoral immune response elicited to nHgbA (13).…”
mentioning
confidence: 99%